Nonlinear selection and the evolution of variances and covariances for continuous characters in an anole (2010)
The pattern of genetic variances and covariances among characters, summarized in the additive genetic variance?covariance matrix, G , determines how a population will respond to linear natural selection. However, G itself also evolves in response to selection. In particular, we expect that, over time, G will evolve correspondence with the pattern of multivariate nonlinear natural selection. In this study, we substitute the phenotypic variance?covariance matrix (P ) for G to determine if the pattern of multivariate nonlinear selection in a natural population of Anolis cristatellus , an arboreal lizard from Puerto Rico, has influenced the evolution of genetic variances and covariances in this species. Although results varied among our estimates of P and fitness, and among our analytic techniques, we find significant evidence for congruence between nonlinear selection and P , suggesting that natural selection may have influenced the evolution of genetic constraint in this species.